Multidisciplinary model for hospital-territory integrated management of patient with bone fragility: primary and secondary prevention of fractures according to severity and complexity - C. Caffetti; L. Bogliolo; G. Giuffrè; A. Sozzi; L. Degli Esposti; E. Bellis; C. Montecucco; F. Reitano; A. Triarico; S. Silva; M. Bejor; A. Muzzi; et al. (PAGEPress Publications, 2020)
The aim of this study was to promote the construction of a real network and a shared diagnostic and therapeutic management model between hospitals and out-of-hospital healthcare services to capture as many patients with bone fragility as possible. Starting from the analysis of the clinical competences present in the province of Pavia, the bone specialists (BSs) organized some educational events involving both general practitioners (GPs) and hospital specialists. The Fracture Liaison Service (FLS) model, the revision of Note 79, the national plan for chronicity and the health reform of the Lombardy Regional Authority supported the structure of our model, in which the roles of clinicians are well defined and based on the complexity and severity of patients. In our method the GP has a central role as clinical manager, facilitating patient management and communication between the specialists and the BS. In January 2019, the Therapeutic Care Diagnostic Path (PDTA) shared between 2 bone specialists (BSs), 9 GPs, as reference treaters, and a multidisciplinary group of 25 specialists of the Province of Pavia was defined. The strategic directions of the two largest public hospitals in Pavia have supported the PDTA, which was validated by the quality departments of the hospitals themselves. Finally, sixty GPs belonging to the network have joined the PDTA. This model is the first example of integrated management between hospitals and out-of-hospital healthcare services for the primary and secondary prevention of fragility fractures (FF), where the GPs play a pivotal role as managers and supervisors to ensure proper care to chronic patients according to their levels of severity.